Model Corporate Social Responsibility di Sekitar Wilayah Kerja Perusahaan Migasjob Pertamina Talisman (OK) Ltd. Kabupaten Ogan Komering Ulu Provinsi Sumatera Selatan - Bomantara Zaelani Bomantara (Jurnal Empirika, 2016)
Corporate Social Responsibility or CSR lately become increasingly hot topic discussed. Many companies do not succeed or fail in carrying out CSR programs are one indicator is the number of complaints or protests from people around the operation areas of the company. This failure caused a lot of election CSR activities are not appropriate. Before undertaking CSR activities, the company must perform mapping the needs of the targeted community activities then disseminate to the CSR activities will be conducted. Selection of CSR activities to be undertaken must be based on the principles of CSR that help engage the community and sustainable In the election of CSR activities in addition to mapping the needs of society, considered also the community's ability to run these activities and CSR activities that will be carried out can result in the not too long. It's menumbuhkaan trust and the community's ability to run CSR programs conducted with the company. At the start of the company's CSR activities should help activities from upstream to downstream and slowly help or participation of the company minus. At the beginning of activity of the company is the driving force of activities and is slowly turning into a supervisory activity undertaken CSR Program.